AFFIRMATIVE ACTION POLICY ON WOMEN'S REPRESENTATION IN THE HOUSE OF REPRESENTATIVES - Talaba, Renals (Universitas Airlangga, 2024)
Affirmative policies and the low representation of women in the House of Representatives (DPR) indicate obstacles within the design of the electoral and party systems. Therefore, this study aims to identify the challenges posed by the operation of technical variables in both indirect and direct electoral systems regarding women's representation in the DPR. To achieve this goal, the study employs the Rational Choice Neoinstitutionalism (RCN) approach. This approach seeks to understand how systems, structures, and institutions are designed and interact to achieve specific objectives. The purpose of political institutionalization is to make political institutions more accountable, transparent, controlled, responsive, participatory, and rooted in the rule of law. This study adopts a literature review method, summarizing and analyzing ideas from various sources to develop an understanding and theory about affirmative policies, followed by a review of the operationalization of technical electoral variables within electoral regulations. The findings reveal that affirmative policies in Indonesia's democratic electoral system do not guarantee women's representation in the DPR. This is because affirmative policies are focused solely on electoral formulas, while other technical variables are deemed disadvantageous. This is evident from the number of women in the DPR from the 2004 to 2024 elections, where women's representation has not yet reached the critical mass threshold